Pengembangan Pendidikan Islam Integratif di Indonesia; Kajian Filosofis dan Metode Implementasi - Fiska Ilyasir (Universitas Alma Ata, 2017)
This paper attempts to discuss development of an integrated system of Islamic education in Islamic educational institutions in Indonesia. After reviewing the problems of Islamic education as well as alternative solutions that may able to solve these problems, the authors conclude that in dealing with changes in modern society, internally and independently, Islamic educational institutions must resolve the issues of dichotomy, and also related to the purpose and functions of their institutions.Islamic educational institutions must develop a new design of an integrated Islamic education. Some steps of these redesign is expected to be a solution to this problem, including reviewing the philosophical foundation of the institutions, integrating Islamic values into the learning process, and also it's implementation.On the philosophical level, educational institutions should revitalize their institutional goals, so that it will be a reference for the institution to implement the educational process. Whereas in the implementation stage, the institution must carry out these integration of Islamic education to the learning system, including the learning objectives, materials, human resources, or the environment.